Role of food and nutrition in pathogenesis and prevention of Hashimoto’s thyroiditis - Puszkarz, Irena; Guty, Edyta; Stefaniak, Iwona; Bonarek, Aleksandra (Journal of Education, Health and Sport, 2018)
Background: Over 300 million people around the world have thyroid problems. Hashimoto’s thyroiditis is the most common reason for hypothyroidism among people aged 45 to 65, mostly women. Hashimoto’s thyroiditis is a mysterious immune-mediated disease and its reason is still not fully clear. According to specialists nutritional habits have impact on the development of the disease. Fatigue, reduction of exercise capacity, movement deceleration, drowsiness, hair and eyebrow loss, dry skin, nail fragility, feeling cold and chronic constipation are dominant feelings in the clinical picture of the disease. The objective of the paper is indication of food ingredients that support thyroid gland activity as well as those that should be limited. Content: In many publications it is emphasized that right nutrition and proper selection of nutrients are necessary in occurring and development of Hashimoto’s thyroiditis. The diet of patients with hypothyroidism should be based on increased content of complete protein, polyunsaturated fatty acids as well as carbohydrates with a low glycaemic index. Consumption of complex carbohydrates which provide the most of mineral nutrients, vitamins and dietary fibres is recommended. The supply of vitamins and mineral nutrients is important due to their impact on secretory activity of the thyroid. They include iodine, iron, selenium and zinc as well as vitamins: A, D, E, B2, B3 and B12. Existence of relation between vitamin D deficiency and the risk of development of autoimmune thyroiditis is also indicated. Summary: The diet of patients with Hashimoto’s thyroiditis should be considered in a complex way, including hormone deficiency as well as changes in diet and supplementing it in necessary mineral nutrients and vitamins. Therefore education regarding the rules of proper nutrition should be a component of the process of treatment.